Soft Metalens for Broadband Ultrasonic Focusing through Aberration Layers - Erqian Dong; Tianye Zhang; Jinhu Zhang; Xiaochun Su; Sichao Qu; Xin Ye; Zhanyuan Gao; Chengtian Gao; Jiangang Hui; Zhanxiang Wang; Nicholas X. Fang; Yu Zhang (Nature Communications)
Abstract Aberration layers (AL) often present significant energy transmission barriers in microwave engineering, electromagnetic waves, and medical ultrasound. However, achieving broadband ultrasonic focusing through aberration layers like the human skull using conventional materials such as metals and elastomers has proven challenging. In this study, we introduce an inverse phase encoding method employing tunable soft metalens to penetrate heterogeneous aberration layers. Through the application of effective-medium theory, we determined the refractive index of micro-tungsten particles in silicone elastomer, closely aligning with experimental findings. The soft metalens allows for transmission across broadband frequencies (50 kHz to 0.4 MHz) through 3D-printed human skull models mimicking aberration layers. In ex vivo transcranial ultrasound tests, we observed a 9.3 dB intensity enhancement at the focal point compared to results obtained using an unfocused transducer. By integrating soft materials, metamaterials, and gradient refractive index, the soft metalens presents future opportunities for advancing next-generation soft devices in deep-brain stimulation, non-destructive evaluation, and high-resolution ultrasound imaging.